L’Homme Sain (Fiep Bulletin - online, 2015)
Taking also into consideration the scientific authority of the author who is correspondent Member of the Bulgarian Academy of Sciences and President of the Scientific and Methodological Council of the Bulgarian Union of Physical Education, the article which is summarized, has a great interest.